2022
DOI: 10.1002/jcu.23382
|View full text |Cite
|
Sign up to set email alerts
|

Fetal brain biometry and cortical development after maternal SARS‐CoV‐2 infection in pregnancy: A prospective case–control study

Abstract: Objectives To assess cerebral growth and the development of fetal cortex using neurosonography in fetuses from pregnancies experiencing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) according to infection timing. Methods Pregnancies with by SARS‐CoV‐2 during first and second trimesters were prospectively studied and matched with unaffected controls. Enclosed women underwent neurosonography at 30–34 weeks of gestation and corpus callosum (CC) and cerebella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…showed in a biometry of fetal brains after SARS-CoV-2 infection using ultrasound that general brain growth and cortical development were not affected. 32 However, our findings on abnormalities in the fetal brain are based on vascular events. The latter is particularly interesting when considering the interplay in the excretion of fetally produced cholephilic organic anions, which are potentially toxic, and in the elimination of which both placenta and fetal liver play an essential role.…”
Section: Discussionmentioning
confidence: 75%
“…showed in a biometry of fetal brains after SARS-CoV-2 infection using ultrasound that general brain growth and cortical development were not affected. 32 However, our findings on abnormalities in the fetal brain are based on vascular events. The latter is particularly interesting when considering the interplay in the excretion of fetally produced cholephilic organic anions, which are potentially toxic, and in the elimination of which both placenta and fetal liver play an essential role.…”
Section: Discussionmentioning
confidence: 75%
“…19 It has been shown that fetal growth, cardiac function and cerebral growth are not affected by maternal infection. [20][21][22] However, there are few studies on the effects of maternal COVID-19 infection severity on the fetus, and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women with COVID-19 have been reported to have higher anxiety levels due to concerns about negative effects on their newborns 19. It has been shown that fetal growth, cardiac function and cerebral growth are not affected by maternal infection 20–22. However, there are few studies on the effects of maternal COVID-19 infection severity on the fetus, and further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…During neurosonographic evaluation, measurements related to the corpus callosum (CC), subarachnoid space, insula, and parieto-occipital fissure depths in the axial image are primarily used in neurosonographic research. [9][10][11][12] However, further studies are needed to comprehensively assess the fetal intracranial structures and spaces with additional planes to increase the reliability of the correlation between the detected measurement differences and structural defects, especially in women with DM, which has a remarkable potential to cause fetal brain abnormalities. 8,13 To date, no published study has undertaken an assessment of brain structures in women with DM at gestational ages beyond 20 weeks, with particular emphasis on simultaneous measurements of CC width and depth in the midsagittal image; and lateral craniocortical (LCC) and posterior craniocortical (PCC) widths of the subarachnoid space and insular and parieto-occipital fissure depths in the axial image.…”
Section: Introductionmentioning
confidence: 99%
“…The various intracranial structures and spaces, which technical advances in neurosonography have made it possible to measure, are increasingly being taken into account in the study of disorders of brain development during fetal life. During neurosonographic evaluation, measurements related to the corpus callosum (CC), subarachnoid space, insula, and parieto‐occipital fissure depths in the axial image are primarily used in neurosonographic research 9–12 . However, further studies are needed to comprehensively assess the fetal intracranial structures and spaces with additional planes to increase the reliability of the correlation between the detected measurement differences and structural defects, especially in women with DM, which has a remarkable potential to cause fetal brain abnormalities 8,13 .…”
Section: Introductionmentioning
confidence: 99%